Hubungan Antara Kecerdasan Spiritual Dengan Solidaritas Mekanik Umat Beragama (Studi Kasus Di Desa Karangsari, Kec. Cluwak, Kab. Pati, Jawa Tengah) - Sutrisno Sutrisno; Jeny Harianto; Jo Priastana (Dhammavicaya : Jurnal Pengkajian Dhamma, 2020)
Research on the relationship between spiritual intelligence and the mechanical solidarity of religious people (Case Study in Ngawen Village, Cluwak District, Pati Regency, Central Java) is important research for the development of religious life in Indonesia. That is because, the appreciation of religion is something that accompanies religious life, but at the same time religion also requires a strong bond of brotherhood. This study tries to look at the relationship between the individual and social dimensions of religious life. This study discusses the discussion of spiritual intelligence with the mechanical solidarity of Buddhists in Karangsari Village, Kec. Cluwak, Kab. Starch. Obtained from ex-post facto research because the facts or symptoms that were collected already existed before the respondent or symptoms appeared without the presence of consultation. The data in this study were obtained based on respondents' answers in the questionnaire research. Data collected includes ordinal data. This data refers to the resolution or classification of responses to instrument approval. This research proves that there is no difference between Spiritual Intelligence and Mechanical Solidarity. Based on data processing, the results of the relationship between the two variables are positive, but in the low category. The low relationship between Spiritual Intelligence and Mechanical Solidarity can be interpreted as Buddhist social piety, not fully relying on the internal values of Buddhism. However, awareness can be determined by values and norms that are given together. The facts that occur in the field can show a phenomenon that is getting stronger and closer, the social ties of society, the deeper the religious feelings and the feelings about the sacred things that accompany each manifestation are gathered